Media Digital Interaktif sebagai Inovasi Pembelajaran PAI untuk Meningkatkan Literasi Keagamaan Siswa di Era Modern - Ghani, Athaillah Abdul (LaKaspia, 2025)
The rapid advancement of digital technology has significantly transformed the landscape of education, including the field of Islamic Religious Education (PAI). In this digital era, PAI learning is required to adapt in order to remain relevant to the needs and learning styles of modern students. This study aims to analyze how interactive digital media can serve as an innovative approach to enhance students’ religious literacy in Islamic education. The research employs a library research method by reviewing academic literature, scholarly journals, and previous studies related to digital learning and Islamic pedagogy. The collected data were analyzed descriptively and analytically to synthesize theoretical perspectives on digital literacy and Islamic education. The results indicate that interactive digital media play a crucial role in improving students’ motivation, engagement, and understanding of Islamic values. The use of educational videos, digital learning applications, and interactive platforms enriches the learning experience through visual and participatory approaches. However, challenges remain regarding teachers’ limited capacity to integrate Islamic values into digital content and the lack of systematic implementation guidelines. The study concludes that the success of digital learning innovation depends largely on teachers’ ability to manage technology creatively, contextually, and spiritually. This research contributes to strengthening a new paradigm in Islamic education that positions digital media as a transformative tool for building critical, reflective, and contextual religious literacy in the modern era.